2021
DOI: 10.1155/2021/8522303
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Terrible Triad Variant Associated with an Essex-Lopresti Injury

Abstract: Essex-Lopresti injuries and terrible triad injuries of the elbow are rare injuries that typically result from high-energy trauma such as falling from a height or a motor vehicle collision. However, the combination of an Essex-Lopresti injury and terrible triad injury is unique and poses a significant challenge for treatment as these injuries are independently associated with poor functional outcomes if they are not acutely diagnosed. We describe a case of a 19-year-old who presented with an unusual variant of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Similarly, Luis M. Salazar et al [10] in their case report mentions about associated ipsilateral Essex-Lopresti injury with terrible triad, which was fixed with IJS system, radial head was fixed with smaller screws. Patient had a good outcome following the surgery [10] .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Luis M. Salazar et al [10] in their case report mentions about associated ipsilateral Essex-Lopresti injury with terrible triad, which was fixed with IJS system, radial head was fixed with smaller screws. Patient had a good outcome following the surgery [10] .…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, Luis M. Salazar et al [10] in their case report mentions about associated ipsilateral Essex-Lopresti injury with terrible triad, which was fixed with IJS system, radial head was fixed with smaller screws. Patient had a good outcome following the surgery [10] . One case out of 15 cases as reported by Bhavsar et al 9 had a terrible triad variant injury (i.e., medial condyle fracture with LCL injury along with classical triad) further details like the mechanism of injury were not specified.…”
Section: Resultsmentioning
confidence: 93%
“…There is limited evidence for acute management of terrible triad injury with associated Essex-Lopresti. Salazar et al 29 reported on a 19-year-old with this injury pattern and concomitant distal radius fracture. The LCLC was repaired, the radial head fracture was fixed with screws, a dorsal spanning plate was applied to the distal radius, and the IJS was used for temporary stabilization.…”
Section: Discussionmentioning
confidence: 94%
“…5 ). 29 , 32 The proximal radius was prepared for arthroplasty according to the previously described technique (Align; Skeletal Dynamics, Miami, FL, USA). 11 , 21 Prosthetic length was determined in relation to the corner formed by the lesser and greater sigmoid notch when evaluated on a true anteroposterior fluoroscopic image with the forearm in supination.…”
Section: Case Reportmentioning
confidence: 99%
“…Our initial search revealed 47 eligible articles ( 6 , 7 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ) ( Fig. 1 ), of which 27 were case reports and 20 were case series.…”
Section: Resultsmentioning
confidence: 99%